Genetic characterization and whole-genome sequencing-based genetic analysis of influenza virus in Jining City during 2021–2022 - Li, Libo; Liu, Tiantian; Wang, Qingchuan; Ding, Yi; Jiang, Yajuan; Wu, Zengding; Wang, Xiaoyu; Dou, Huixin; Jia, Yongjian; Jiao, Boyan (Frontiers in Microbiology, 2023)
Background The influenza virus poses a significant threat to global public health due to its high mutation rate. Continuous surveillance, development of new vaccines, and public health measures are crucial in managing and mitigating the impact of influenza outbreaks. Methods Nasal swabs were collected from individuals with influenza-like symptoms in Jining City during 2021-2022. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect influenza A viruses, followed by isolation using MDCK cells. Additionally, nucleic acid detection was performed to identify influenza A H1N1, seasonal H3N2, B/Victoria, and B/Yamagata strains. Whole-genome sequencing was conducted on 24 influenza virus strains, and subsequent analyses included characterization, phylogenetic construction, mutation analysis, and assessment of nucleotide diversity. Results A total of 1,543 throat swab samples were collected. The study revealed the dominance of the B/Victoria influenza virus in Jining during 2021-2022. Whole-genome sequencing showed co-prevalence of B/Victoria influenza viruses in the branches of Victoria clade 1A.3a.1 and Victoria clade 1A.3a.2, with a higher incidence observed in winter and spring. Comparative analysis demonstrated lower similarity in the HA, MP, and PB2 gene segments of the 24 sequenced influenza virus strains compared to the Northern Hemisphere vaccine strain B/Washington/02/2019. Mutations were identified in all antigenic epitopes of the HA protein at R133G, N150K, and N197D, and the 17-sequence antigenic epitopes exhibited more than 4 amino acid variation sites, resulting in antigenic drift. Moreover, one sequence had a D197N mutation in the NA protein, while seven sequences had a K338R mutation in the PA protein. Conclusion This study highlights the predominant presence of B/Victoria influenza strain in Jining from 2021 to 2022. The analysis also identified amino acid site variations in the antigenic epitopes, contributing to antigenic drift.